Generalised or specialised simulation? Comparing types of Discrete-event simulation software and possibilities for increasing the value proposition - Eriksson, Martin; Ferning, Alexander (My University, 2023)
Discrete-event simulation has emerged as a powerful tool for analysing dynamic sys tems. Numerous software companies have developed their own software solutions with different niches, strengths and weaknesses. Users, however, tend to keep using the same software, no matter what they will model. This master’s thesis compares and assesses general and specialised DES software on numerous parameters. An in dustrial use case was modelled, supported by interviews and surveys conducted with participants from academia and industry. An existing model was recreated using specialised software, based on the provided model specifications. The throughput observed in both models was similar, with differences attributed to different under lying model assumptions. Both software types have their advantages and disadvan tages, and it is important for users to be aware of these before selecting which one to use. Each software was deemed reliable alternatives for usage in a professional set ting. Two different model-building approaches were identified between the software users. A resource-oriented top-down approach was more common in the specialised, while a load-oriented bottom-up approach was more common in the generalised soft ware. Through interviews and a literature review, potential use cases to increase the value proposition of DES were explored and competencies, challenges, enabling technologies and architecture were identified. The interviews revealed some profes sional scepticism regarding adopting a complete Digital Twin approach, utilizing the DES model as a simulator within the Digital Twin. A promising alternative, Digital Shadow, was identified as an attractive alternative. Potential scenarios, and how they could be implemented were suggested using dynamic production planning.
Keywords: Digital Twin, Discrete-event simulation, Digital Shadow, Comparison of simulation software, Generalised simulation software, Specialised simulation soft ware